Analisis Komparasi Hukum Akad Peer to Peer Lending - St. Nurafni Mutmainnaturrahmah; Mabruri Andatu; Ahmad Muti (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study analyzes the comparison of peer-to-peer (P2P) lending contract law in the perspective of positive law and Islamic law. Major problems in the industry include the risk of default, contract defects, and a lack of transparency. The research method used is literature research. The results show that positive laws provide a framework for consumer protection, but are often inadequate in protecting vulnerable parties. On the other hand, Islamic law emphasizes justice and the prohibition of usury, although the practice in the field is not yet fully appropriate. The study recommends collaboration between regulators and service providers to create a fair and law-abiding system. This is expected to contribute to the development of P2P lending policies and practices that are more sustainable and in accordance with sharia principles.